2019
DOI: 10.1089/neu.2018.5962
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cardiovascular Dysfunction in a Rat Spinal Cord Crush Model and Responses to Serotonergic Interventions

Abstract: Selection of a proper spinal cord injury (SCI) rat model to study therapeutic effects of cell transplantation is imperative for research in cardiovascular functional recovery, due to the local harsh milieu inhibiting cell growth. We recently found that a crushed spinal cord lesion can minimize fibrotic scarring and grafted cell death compared with open-dura injuries. To determine if this SCI model is applicable for studying cardiovascular recovery, we examined hemodynamic consequences following crushed SCI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Nonetheless, we cannot directly rule out the possibility that viable cells within the graft produced abundant 5-HT that diffused into CSF (Tadepalli et al, 1977), allowing for longer-distance transport to SPNs. Since recent studies found that stimulating spinal 5-HT 2A receptors improves basal hemodynamic and reflexes in SCI rats (Cormier et al, 2010;Trueblood et al, 2019), excess 5-HT in the CNS may maintain a certain degree of cardiovascular performance after serotonergic projections are interrupted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, we cannot directly rule out the possibility that viable cells within the graft produced abundant 5-HT that diffused into CSF (Tadepalli et al, 1977), allowing for longer-distance transport to SPNs. Since recent studies found that stimulating spinal 5-HT 2A receptors improves basal hemodynamic and reflexes in SCI rats (Cormier et al, 2010;Trueblood et al, 2019), excess 5-HT in the CNS may maintain a certain degree of cardiovascular performance after serotonergic projections are interrupted.…”
Section: Discussionmentioning
confidence: 99%
“…After administration of ketanserin, CRD elicited only a subtle pressor response in all three groups of injured animals. This may be due to the necessity of these receptors for sympathetic reflexes or peripheral responses (Danzebrink and Gebhart, 1991;Trueblood et al, 2019). Therefore, we then turned to retransecting the spinal cord below the injury to evaluate the role of RN-NSC grafts in the improved cardiovascular function we observed.…”
Section: Pharmacological Interventions and Spinal Cord Retransection mentioning
confidence: 99%
“…Superficial laminae and lamina X [17] Antinociception, pronociception [17] Micturition [398,399] SCH 23390 [398][399][400]402,403], SCH 39166 [401,404] Aripiprazole [405], apomorphine [300,398,400,406], SKF 83959…”
Section: Dopaminergic Fiber Pathwaysmentioning
confidence: 99%
“…Loss of supraspinal 5-HT + fibres play a key role in inducing CV dysregulation including contributing to the development of AD and hypotension observed post-SCI [33,48]. Other models of SCI which have explored the relationship between 5-HT + preservation and CV function post-SCI include complete crush [25], and partial transection [49] models of SCI at the T4 level. Neither crush injury nor partial transection reported reduced MAP despite showing reduced/absent density of serotonergic fibres caudal to the injury.…”
Section: T3 Moderately-severe Contusion Injury Interrupts Descending Pathwaysmentioning
confidence: 99%
“…For the CV system, a number of rat models have been developed to study the CV consequences of SCI, as well as the efficacy of various therapeutics. Two of the models that have received most traction are the T3/T4 complete transection model or a very severe midline contusion injury [23,24], though others also exist [25]. Both transection and severe contusion injuries (i.e., 400 kdyn contusion model) have been effective in producing changes to the CV function that mimic those observed clinically with high-lesion SCI, such as the presence of pronounced hypotension, reduced systolic cardiac function, and the presence of autonomic dysreflexia and orthostatic intolerance [23,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%